2008
DOI: 10.2500/ajr.2008.22.3245
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validation of a Low-fidelity Endoscopic Sinus Surgery Simulator

Abstract: Our model was unable to demonstrate clear construct validity at this time. Materials and structural modifications are in progress. Pending further validation, its low-cost construction possesses potential for integration into otolaryngology residency curricula. Assessment of the simulator's ability to improve surgical skill is also planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…21 These range from low to very high fidelity, but the ideal model does not yet seemingly exist. Leung et al 22 and Wais et al 23 used common materials to create a low-fidelity simulator. They demonstrated improvements in performing surgical tasks but did not establish construct validity.…”
Section: Discussionmentioning
confidence: 99%
“…21 These range from low to very high fidelity, but the ideal model does not yet seemingly exist. Leung et al 22 and Wais et al 23 used common materials to create a low-fidelity simulator. They demonstrated improvements in performing surgical tasks but did not establish construct validity.…”
Section: Discussionmentioning
confidence: 99%
“…3 For these reasons, in the present study, we used the VR simulator for the objective assessment of basic endoscopic skills before and after EES training, as previous investigations had used it for the same purpose in laparoscopic training. 10,12,17,22,23 We developed a prototype of a box trainer for learning the psychomotor skills required for EES. We revealed that the training using this box trainer could improve psychomotor skills for novices.…”
Section: Discussionmentioning
confidence: 99%
“…However, effective training models for sinus surgery should not only communicate geometry (anatomy), but also haptic skills, as well as “characteristics of incision” [677], [678], [679]. Conversely, abstract training of manual dexterity without any concrete relation to sinus anatomy is not sufficient, either [680], [681]. Students find it most difficult to master three-dimensional endoscopic anatomy, especially in the case of irregularities (previous operations) or manipulation controlled by optics revealing different angles of view [680].…”
Section: Training Issuesmentioning
confidence: 99%